Two Heavy Rainfall Types over the Korean Peninsula in the Humid East Asian Summer Environment: A Satellite Observation Study - Song, Hwan-Jin; Sohn, Byung-Ju (Monthly weather review, 2015)
A total of 10 years (2002–11) of Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (PR) reflectivities, signaling heavy rainfall (>10 mm h−1), were objectively classified by applying the K-means clustering method in order to obtain typical reflectivity profiles associated with heavy rainfall over East Asia. Two types of heavy rainfall emerged as the most important rain processes over East Asia: type 1 (cold type) characterized by high storm height and abundant ice water under convectively unstable conditions, developing mostly over inland China; and type 2 (warm type) associated with a lower storm height and lower ice water content, developing mostly over the ocean. These two types also show sharp contrasts in relation to their seasonal changes and in the diurnal variation of frequency maxima, in addition to other contrasting meteorological parameters. The PR-derived heavy rain events were observed over the Korean peninsula and their spatiotemporal evolution was examined using 10-yr composites of 11-μm brightness temperature from geostationary satellites and Interim ECMWF Re-Analysis (ERA-Interim) data. Cold-type heavy rainfall over Korea is characterized by an eastward moving cloud system with an oval shape while the warm type shows a comparatively wide spatial distribution over an area extending from the southwest to northeast. Overall the warm-type process appears to link the low-level moisture convergence area to the vertically aligned divergence area formed over the jet stream level. This setup continuously pushes air upward under moist-adiabatically near-neutral conditions and thus yields heavy rainfall. As warm-type heavy rainfall persists longer, it is considered to be more responsible for flood events occurring over the Korean peninsula.